156k views
0 votes
100 ptsss 7x + 3x − 18 = 6(x + 3)

could you also show the steps you took and where u took them???
Distributive Property
Subtraction Property of Equality
Combine Like Terms
Multiplication Property of Equality
Division Property of Equality
Given
Addition Property of Equality

User ThaJeztah
by
4.6k points

1 Answer

4 votes

Answer:

X = 9

Explanation:

7x + 3x - 18= 6(x+3)

7x + 3x = 10x - 18 = 6(x+3)

10x - 18 = 6(x+3) convert that into (distribute) 6x + 18

+18 +18 (add 18 to both sides)

Simplify: 10x + 6x + 36 (subtract 6x form both sides)

-6 -6

Simplify: 4x = 36 (divide each by 4)

_ _

4 4

Simplify: x = 9

User Nicholas Harder
by
4.5k points